REFLECTIVE THINKING AND THE TRADITION OF ISLAMIC JURISPRUDENCE - Muhlison Siregar (Program Pascasarjana UIN Sumatera Utara, 2021)
Reflective thinking can occur when a person experiences confusion, obstacles or doubts in solving a problem he faces. Basically, reflective thinking is a person's ability to select the knowledge that has been owned and stored in his memory to solve any problems faced to achieve his goals. The method used to obtain the data needed in this discussion is the Library Research method. The result is that as a source of value, the Koran is strived to continue to be understood and actualized in the daily lives of Muslims. In line with this, humans were created with full limitations. No matter how great a human being, it is not certain that he has actually arrived at the